Desenvolvimento de sistema automatizado com troca de dados via rede ethernet no processo de transporte na fabricação de latas - Nunes Neto, Bianor (2013)
This project aims to perform the relate of a process of transport of cans, with full control using PLC and HMI, making the process more efficient, reducing losses and having more reliability in the final result, through of interaction Ethernet network with other networks of existing fields (mainly Devicenet). The use of Ethernet is an option very viable by be considered easy handling and great coverage the compatibility between devices. Thus, communication between equipment becomes easier and faster with the use of this technology.